Understanding the Dynamics of Human Papillomavirus and Diagnostic Discrepancies in Cervical Pathology: A Single Center Experience - Milena Zamurovic; Ana Tomic; Aleksandra Pikula; Sara Simanic; Aleksandra Knezevic; Marko Jankovic; Milan Lackovic; Elena Djakovic; Marija Rovcanin (Diagnostics, 2023)
Cervical cancer (CC) is the most prevalent gynecological malignancy and a leading cause of death among women. It is primarily caused by human papillomavirus (HPV) infection, with 99.7% of cases showing high-risk HPV genotypes. This study sheds light on HPV dynamics as well as the discrepancies of different CC screening modalities results while highlighting factors that may have contributed to such a scenario. Moreover, we underscore the importance of the non-viral etiology of CC as well. We examined the current trends of HPV infection and its effects on cervical health in women treated at a tertiary care center in Belgrade, Serbia. Patients with abnormal colposcopy findings like dysplasia and re-epithelization were more likely to test negative for HPV (p < 0.001). Interestingly, women with a positive Pap smear tested HPV negative significantly more often (p = 0.041). Finally, HPV-positive individuals were more likely to have CIN I and II histologies (p < 0.001), while CIN III occurred equally in women with and without the virus. It may be inferred that inconsistencies in detecting HPV and the presence of cervical lesions may eventually result in adjustments to screening guidelines, as is crucial to adopt a meticulous approach to promote periodical CC screening, as initial samples may test negative for HPV.